Refining the Focus on Faculty Diversity in Postsecondary Institutions: New Directions for Institutional Research, Number 155 - Xu, Yonghong Jade (J-B IR Single Issue Institutional Research, 2012)
Faculty diversity is gaining unprecedented emphasis in the mission of colleges and universities, and institutional researchers are being pushed for relevant data. This volume examines faculty diversity from a variety of perspectives.Together, they constitute a comprehensive outlook on the subject, highlighting factors including racial background, gender, citizenship, employment status, and academic discipline, and examining how growing diversity has affected the work experience and productivity of faculty and the learning outcomes of students. Special attention is given to international and nontenure-track faculty members, two groups that have experienced rapid growth in recent years. The authors:Present empirical evidence to support the increasing importance of faculty diversity in institutional researchShow the need for actively tracking the changes in diversity over timeHighlight the critical role of research methodology in all such work.This is the 155th volume of this Jossey-Bass quarterly report series. Always timely and comprehensive, New Directions for Institutional Researchprovides planners and administrators in all types of academic institutions with guidelines in such areas as resource coordination, information analysis, program evaluation, and institutional management.